Method for preparing gradient heterogeneous lamellar structure titanium alloy
By combining heat treatment, corrugated rolling and multi-pass flat rolling processes, a gradient heterogeneous sheet-structure titanium alloy is formed, and through shot peening, the problem that traditional titanium alloys are difficult to take into account both high tensile strength and plastic toughness is solved, and excellent performance under complex working conditions is achieved.
Patent Information
- Application Number
- CN202411726553.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-18
AI Technical Summary
The homogeneous ultrafine crystal titanium alloy obtained by traditional large plastic deformation-heat treatment processes is difficult to take into account high tensile strength and good plastic toughness, which limits its application in complex service conditions.
A combination of heat treatment, corrugated rolling and multi-pass flat rolling is used to form a gradient heterogeneous sheet structure titanium alloy, and the surface state is improved by shot peening.
It realizes that titanium alloy maintains good plastic toughness while maintaining high tensile strength, and further improves tensile strength through shot peening, which is suitable for complex engineering applications.
Smart Images

Figure CN119640174A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, and in particular to a method for preparing a gradient heterogeneous lamellar structure titanium alloy. Background Art
[0002] Although the homogeneous ultrafine-grained titanium alloy obtained by traditional large plastic deformation-heat treatment process can improve strength, it is difficult to take into account both plasticity and toughness to adapt to complex service conditions, which becomes an obstacle to practical engineering applications. How to obtain titanium alloys with good strength and plasticity matching is still an urgent problem to be solved in this field. Summary of the invention
[0003] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a gradient heterogeneous lamellar structure titanium alloy, so that the gradient heterogeneous lamellar structure titanium alloy has the advantages of high tensile strength and good plastic toughness. In addition, the method of the present application combines heat treatment, rolling and shot peening, the preparation process is mature, and the equipment requirements are low, which is conducive to low-cost industrial production.
[0004] To solve the above problems, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a gradient heterogeneous lamellar structure titanium alloy comprises the following steps:
[0006] The titanium alloy slab is kept above the β transformation temperature for at least 30 minutes, and water-cooled to room temperature to obtain a first slab;
[0007] The first blank is heated to 700-850° C. and kept at this temperature for at least 5 minutes, and then rolled with a corrugated roller so that corrugated surfaces are formed on the upper and lower ends of the plate to obtain a second blank;
[0008] The second blank is heated to 650-800° C. and kept at this temperature for at least 5 minutes, and subjected to multiple passes of flat rolling to flatten the corrugated surface, thereby obtaining a third blank;
[0009] The flattened surface of the third blank is polished, and the polished end face is shot peened to obtain a gradient heterogeneous lamellar structure titanium alloy.
[0010] In some possible embodiments, the holding temperature for obtaining the first blank is 1000-1100° C., and the holding time is 30-120 minutes.
[0011] In some possible embodiments, the heat preservation time for obtaining the second blank and the third blank is 5-20 minutes.
[0012] In some possible embodiments, in the step of obtaining the second blank, the corrugation rolling reduction is 13%-17%, and the total rolling deformation is 77%-82%.
[0013] In some possible embodiments, the reduction in a single pass of flat rolling is 17%-39%, and the total reduction in flat rolling is 55%-65%.
[0014] In some possible embodiments, the parameters of the shot peening process include: a pressure of 0.2-0.8 MPa and a duration of 1-30 minutes.
[0015] In some possible embodiments, in the step of obtaining the second billet, double corrugated roller rolling is used in the first pass, and the corrugated rolling reduction is 17%; in the step of obtaining the third billet, four flat roll rolling passes are performed, and the flat roll rolling reductions in each pass are 19%, 36%, 17% and 31% respectively.
[0016] In some possible embodiments, in the step of obtaining the second billet, two passes of single corrugation roller rolling are performed, and the corrugation rolling reduction is 17% and 13% respectively; in the step of obtaining the third billet, four passes of flat roll rolling are performed, and the flat roll rolling single pass reduction is 22%, 39%, 36% and 25% respectively.
[0017] In some possible embodiments, sandpaper with a grit of at least 1200# or above is used for sanding.
[0018] In some possible embodiments, in the step of obtaining the first blank, the titanium alloy slab is subjected to an anti-oxidation treatment before heating and heat preservation.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] In the present application, a periodic step load is applied to the martensitic structure of the titanium alloy by corrugation rolling to cause the material to undergo large non-homogeneous plastic deformation, forming a lamellar heterogeneous structure of ultrafine grains and coarse grains at the peaks and troughs. Compared with the traditional homogeneous ultrafine grain strengthening structure, it can obtain high tensile strength while maintaining good plastic toughness, and the combined shot peening process can improve the surface state while maintaining the plastic toughness of the matrix, further improving the tensile strength of the titanium alloy. The preparation process of the present invention combines heat treatment, rolling, and shot peening, is mature in preparation, has low equipment requirements, can effectively regulate various parameters in the process links, and realize low-cost industrial production.
[0021] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A flow chart of a method for preparing a gradient heterogeneous lamellar structure titanium alloy provided in one embodiment of the present application.
[0023] Figure 2 This is the heterostructure IPF diagram (inverse pole figure) of the final product of Example 1. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0026] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0027] Reference Figure 1 An embodiment of the present application provides a method for preparing a gradient heterogeneous lamellar structure titanium alloy, comprising the following steps.
[0028] Step S101, keep the titanium alloy slab above the β transformation temperature for at least 30 minutes, and water cool it to room temperature to obtain a first billet. XRD and TEM microstructure analysis show that the first billet is mainly composed of lath α' hexagonal martensite.
[0029] In some embodiments, in this step, the titanium alloy slab is subjected to an anti-oxidation treatment before heating and heat preservation. Exemplarily, the anti-oxidation treatment includes evacuating, passing a protective gas, or applying an alloy high temperature heat treatment coating on the surface of the plate.
[0030] In some embodiments, the holding temperature of the first blank is 1000-1100°C, and the holding time is 30-120 minutes. For example, the holding time can be 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes or 120 minutes, and the range between any two values. The temperature setting is conducive to obtaining a uniform structure. Too high a temperature and too long a holding time will lead to excessively coarse grains, and vice versa, it will lead to uneven and insufficient diffusion of elements.
[0031] Step S102: The first blank is heated to 700-850°C and kept warm for at least 5 minutes, and then rolled with corrugated rollers to form corrugated surfaces on the upper and lower ends of the plate to obtain a second blank. If the rolling temperature is too high, the grains will grow and coarsen, which is not conducive to the formation of ultrafine grain structure. If the temperature is too low and the time is too short, the deformation resistance will be too large, inducing local defects, cracking, severe warping and other problems.
[0032] In some embodiments, the holding time for obtaining the second blank is 5-20 minutes. Too long a holding time will cause the grains to grow and coarsen.
[0033] In some embodiments, in the step of obtaining the second billet, the corrugation rolling reduction is 13%-17%. For example, the corrugation rolling reduction can be 13%, 15%, 17% or a range between any two of the above values, and the total rolling deformation is 77%-82%. For example, the total rolling deformation can be 77%, 78%, 79%, 80%, 82% or a range between any two of the above values. Due to the participation of the corrugation roller, the end face of the sheet is subjected to periodic inhomogeneous plastic deformation, and heterogeneous structures with different grain sizes are formed at the peaks and troughs. In addition, corrugation rolling will generate more plastic deformation heat, accelerate the diffusion movement of atoms, and facilitate dynamic recrystallization. The deformation in the above numerical range is conducive to obtaining a finer grain structure.
[0034] In some embodiments, in the step of obtaining the second blank, double corrugation roller rolling is used in the first pass, and the corrugation rolling reduction is 17%.
[0035] In some embodiments, in the step of obtaining the second blank, two single corrugation roll rollings are performed, and the corrugation rolling reductions are 17% and 13% respectively. The parameters of the above two corrugation rolls are combined with the parameters of the specific flat roll rolling in the subsequent steps to further improve the tensile strength and elongation of the product.
[0036] In other embodiments, a single corrugated roller and a double corrugated roller may be used as working rollers at the same time.
[0037] In some embodiments, the corrugation roller profile is a sine, cosine or any periodic high-order function curve, with an amplitude greater than 5% of the thickness of the plate. By adjusting the surface curve of the corrugation roller, the non-uniform plastic deformation effect applied by the roller is adjusted, and ultimately different grain refinement effects are produced on the plate after corrugation rolling.
[0038] Step S103: The second blank is heated to 650-800°C and kept warm for at least 5 minutes, and multiple passes of flat rolling are performed to flatten the corrugated surface to obtain a third blank. Exemplarily, double-pass flat rolling, three-pass flat rolling, four-pass flat rolling, and more than four-pass flat rolling can be performed. If the rolling temperature is too high, the grains will grow and coarsen, which is not conducive to the formation of ultrafine grain structure. If the temperature is too low and the time is too short, the deformation resistance will be too large, inducing local defects, cracking, severe warping, and other problems.
[0039] In some embodiments, the holding time for obtaining the third blank is 5-20 minutes. Too long a holding time will cause the grains to grow and coarsen.
[0040] In some embodiments, the reduction of a single pass of flat roll rolling is 17%-39%. By way of example, the reduction of a single pass of flat roll rolling can be 17%, 20%, 27%, 30%, 35%, 39% or a range between any two of the above values. The total reduction of flat rolling is 55%-65%. By way of example, the total reduction of flat rolling can be 55%, 60%, 65% or a range between any two of the above values.
[0041] In some embodiments, in the step of obtaining the third blank, four passes of flat roll rolling are performed, and the reduction amount of each pass of flat roll rolling is 19%, 36%, 17% and 31% respectively.
[0042] In some embodiments, in the step of obtaining the third blank, four passes of flat roll rolling are performed, and the reduction amount of each pass of flat roll rolling is 22%, 39%, 36% and 25% respectively.
[0043] By applying different reduction rates during flat roll rolling, the plate can be refined to different degrees and deformed. For example, the greater the reduction applied during rolling, the more obvious the effect of elongation of the coarse grains in the plate along the rolling direction, and the clearer the lamellar grain morphology.
[0044] Step S104: grinding the flattened surface of the third blank, and performing shot peening on the ground end surface to obtain a gradient heterogeneous lamellar structure titanium alloy.
[0045] In some embodiments, sandpaper with a grit of at least 1200# or above is used for sanding to facilitate obtaining a smooth surface.
[0046] In some embodiments, the parameters of the shot peening process include: a pressure of 0.2-0.8 MPa and a duration of 1-30 minutes. The greater the shot peening pressure and the longer the time, the more uniform the stress distribution on the material surface and the greater the thickness of the nano deformation layer. If the pressure is increased or the time is extended, the thickness of the deformation layer and the surface stress will tend to saturate.
[0047] In the present application, a periodic step load is applied to the martensitic structure of the titanium alloy by corrugation rolling to cause the material to undergo large non-homogeneous plastic deformation, forming a lamellar heterogeneous structure of ultrafine grains and coarse grains at the peaks and troughs. Compared with the traditional homogeneous ultrafine grain strengthening structure, it can obtain high tensile strength while maintaining good plastic toughness, and the combined shot peening process can improve the surface state while maintaining the plastic toughness of the matrix, further improving the tensile strength of the titanium alloy. The preparation process of the present invention combines heat treatment, rolling, and shot peening, is mature in preparation, has low equipment requirements, can effectively regulate various parameters in the process links, and realize low-cost industrial production.
[0048] Example 1
[0049] The titanium alloy slab is composed of the following components by mass percentage: Al: 6.08%, V: 4.03%, Fe: 0.14%, Si: 0.013%, C: 0.018%, O: 0.11%, N: 0.0047%, H: 0.0008%. The transformation temperature of the titanium alloy is 975°C, and the original plate size is 100*80*10mm.
[0050] A method for preparing a gradient heterogeneous lamellar structure titanium alloy comprises the following steps.
[0051] Step 1: Take the original titanium alloy slab and apply the alloy steel heat treatment protective coating on the surface to complete the anti-oxidation treatment, then put it into a 1100℃ box-type heating furnace for insulation for 60 minutes, then take it out and quickly place it in cold water to cool to room temperature to obtain the first billet. XRD and TEM microstructure analysis show that the first billet is mainly composed of lath α' hexagonal martensite.
[0052] Step 2: Take the first billet and heat it to 750℃ with the furnace and keep it warm for 20 minutes, and then perform the first double corrugation roller rolling to form a corrugated surface on the upper and lower ends of the plate to obtain the second billet. The corrugation rolling reduction is 17%. The total rolling deformation is 77%. The roll profile curve of the corrugation roller is a circumferential sine curve with an amplitude of 1.4mm, so that it is greater than 5% of the plate thickness.
[0053] Step 3: The sample after corrugation rolling in step 2 is subjected to 4 passes of flat rolling to flatten the corrugated surface. The flat rolling temperature is 650°C, the reduction is 19%, 36%, 17%, and 31%, respectively, the holding time is 15min, 12min, 9min, and 7min, respectively, the final rolling thickness is 2.3mm, and the total flat rolling reduction is 60%, thereby obtaining the third billet.
[0054] Step 4: Use 400#, 800#, 1200#, and 1500# sandpaper to grind the flattened surface of the third blank in turn to remove the paint and oxide film to expose the flat and smooth metal substrate surface, and ultrasonically shot peen the two end surfaces of the plate at a pressure of 0.5Mpa for 3 minutes.
[0055] The titanium alloy plate with gradient heterogeneous lamellar structure prepared in Example 1 has a tensile strength of 1238 MPa and an elongation of 10.8%. Figure 2 shown.
[0056] This application uses an Instron 5969 universal tensile testing machine to test the mechanical properties of each embodiment, and the tensile specimens are processed according to the standard ASTME8M-04. Before the test, the gauge section of the tensile specimen is sanded to remove transverse cracks, and the strain before the deformation of 2% is measured by an extensometer, and the tensile rate is 0.5 mm / min.
[0057] The tensile strength of the original martensitic titanium alloy plate is 1042Mpa and the elongation is 7%.
[0058] Example 2
[0059] The difference from Example 1 is that in step 2, the corrugation rolling temperature is 850°C.
[0060] The titanium alloy plate with a gradient heterogeneous lamellar structure prepared in Example 2 has a tensile strength of 1198 MPa and an elongation of 10%.
[0061] The tensile strength of the original martensitic titanium alloy plate is 1042Mpa and the elongation is 7%.
[0062] Example 3
[0063] The difference from Example 1 is that in step 2 and step 3, the corresponding corrugation rolling and the corresponding flat rolling temperatures are both 700°C.
[0064] The titanium alloy plate with a gradient heterogeneous lamellar structure prepared in Example 3 has a tensile strength of 1208 MPa and an elongation of 8.6%.
[0065] The tensile strength of the original martensitic titanium alloy plate is 1042Mpa and the elongation is 7%.
[0066] Example 4
[0067] The titanium alloy slab is composed of the following components by mass percentage: Al: 6.08%, V: 4.03%, Fe: 0.14%, Si: 0.013%, C: 0.018%, O: 0.11%, N: 0.0047%, H: 0.0008%. The transformation temperature of the titanium alloy is about 975°C, and the original plate size is 100*80*10mm.
[0068] A method for preparing a gradient heterogeneous lamellar structure titanium alloy comprises the following steps.
[0069] Step 1: Take the original titanium alloy plate surface and apply alloy steel heat treatment protective coating to complete the anti-oxidation treatment, send it into a 1100℃ box-type heating furnace for insulation for 60 minutes, then take it out and quickly place it in cold water to cool to room temperature to obtain the first billet. XRD and TEM microstructure analysis show that the first billet is mainly composed of lath α' hexagonal martensite.
[0070] Step 2: Take the first billet and heat it to 750℃ with the furnace and keep it warm for 20 minutes, and then perform two single corrugation roll rolling. The corrugated surface contacts the upper and lower end surfaces of the plate in turn to obtain the second billet. The corrugation rolling reduction is 17% and 13% respectively, and the total deformation after rolling is 82%. The roll profile curve of the corrugation roller is a circumferential sine curve with an amplitude of 1.4mm, so that it is greater than 5% of the thickness of the plate. Step 3: The sample after corrugation rolling in step 2 is subjected to 4 flat roll rolling. The flat rolling temperature is 800℃, the reduction is 22%, 39%, 36%, and 25% respectively, and the holding time is 15min, 10min, 8min, and 5min respectively. The final rolling thickness is 1.8mm, and the total flat rolling reduction is 55%, and the third billet is obtained.
[0071] Step 4: Use 400#, 800#, 1200#, and 1500# sandpaper to grind the flattened surface of the third blank in turn to remove the paint and oxide film to expose the flat and smooth metal substrate surface, and ultrasonically shot peen the two end surfaces of the plate at a pressure of 0.5Mpa for 3 minutes.
[0072] The titanium alloy plate with a gradient heterogeneous lamellar structure prepared in Example 4 has a tensile strength of 1208 MPa and an elongation of 8%.
[0073] The tensile strength of the original martensitic titanium alloy plate is 1042Mpa and the elongation is 7%.
[0074] Example 5
[0075] The difference from Example 1 is that in step 4, the ultrasonic shot peening parameters are: pressure of 0.3 MPa and duration of 3.5 minutes.
[0076] The titanium alloy plate with a gradient heterogeneous lamellar structure prepared in Example 5 has a tensile strength of 1204 MPa and an elongation of 11.4%.
[0077] The tensile strength of the original martensitic titanium alloy plate is 1053Mpa and the elongation is 8%.
[0078] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a gradient heterogeneous lamellar structure titanium alloy, characterized in that: The steps include: The titanium alloy slab is kept above the β transformation temperature for at least 30 minutes, and water-cooled to room temperature to obtain a first slab; The first blank is heated to 700-850° C. and kept at this temperature for at least 5 minutes, and then rolled with a corrugated roller so that corrugated surfaces are formed on the upper and lower ends of the plate to obtain a second blank; The second blank is heated to 650-800° C. and kept at this temperature for at least 5 minutes, and subjected to multiple passes of flat rolling to flatten the corrugated surface, thereby obtaining a third blank; The flattened surface of the third blank is polished, and the polished end face is shot peened to obtain a gradient heterogeneous lamellar structure titanium alloy.
2. The method according to claim 1, characterized in that The first blank is obtained at a holding temperature of 1000-1100° C. and a holding time of 30-120 minutes.
3. The method according to claim 1, characterized in that The heat preservation time of the second blank and the third blank is 5-20 minutes.
4. The method according to claim 1, characterized in that In the step of obtaining the second blank, the corrugation rolling reduction is 13%-17%, and the total rolling deformation is 77%-82%.
5. The method according to claim 4, characterized in that The single pass reduction of flat roll rolling is 17%-39%, and the total flat rolling reduction is 55%-60%.
6. The method according to claim 1, characterized in that The parameters of the shot peening treatment include: a pressure of 0.2-0.8 MPa and a duration of 1-30 minutes.
7. The method according to claim 5, characterized in that In the step of obtaining the second billet, double corrugated roller rolling is used in the first pass, and the corrugated rolling reduction is 17%. In the step of obtaining the third billet, four flat roll rolling passes are performed, and the flat roll rolling single pass reductions are 19%, 36%, 17% and 31% respectively.
8. The method according to claim 5, characterized in that In the step of obtaining the second billet, two passes of single corrugation roller rolling are performed, and the corrugation rolling reduction is 17% and 13% respectively. In the step of obtaining the third billet, four passes of flat roll rolling are performed, and the flat roll rolling single pass reduction is 22%, 39%, 36% and 25% respectively.
9. The method according to claim 1, characterized in that Use sandpaper with a grit of at least 1200# or higher for sanding.
10. The method according to any one of claims 1 to 9, characterized in that In the step of obtaining the first blank, the titanium alloy slab is subjected to an anti-oxidation treatment before heating and heat preservation.